ANALISIS PENENTUAN HARGA POKOK PRODUKSI CABAI RAWIT PADA KELOMPOK TANI MEKAR BERSERI DI DESA SUNGAI PANGKALAN I KECAMATAN SUNGAI RAYA KABUPATEN BENGKAYANG - Al Fathoni, Fikri; Jaurino (Jurnal Akuntansi, Auditing dan Investasi, 2023)
This study entitled "Analysis of Determining the Cost of Cayenne Pepper Production in the MekarBerseri Farmers Group" aims to determine the cost of Cayenne pepper production in the MekarBerseri Farmers Group, where in the Berseri Farmers group has never calculated the cost of chiliproduction and to find out how much Profit earned from the sale of its chili. In processing the datain this study the author uses the Full Costing Method. The production cost of planting cayennepepper according to the full costing method of one production, namely: themcost of raw materialsis Rp. 5,000,000, the cost of auxiliary materials is Rp. 9,450,000, direct labor costs of Rp.54,480,000, and factory overhead costs of Rp. 12,047,500. The total calculation of the cost ofcayenne pepper products is Rp. 80,977,500 or Rp. 10,122.2 Per Kg of Chili. One time the productionof chili planting can produce 8,000 kg of cayenne pepper. The profit obtained from the sale ofcayenne pepper to the Mekar Berseri Farmers Group is Rp. 198,022,500 from the sale of cayennepepper in one production per November-May 2022.